Nicht-invasive Hirnstimulation zur Leistungssteigerung im Sport: Eine neue Form des Neurodopings? - Ragert, P. (Leipziger Sportwissenschaftliche Beiträge, 2016)
Enhancing sporting performance is a desired goal in professional athletes. This can be achieved by strenuous successive practice over many years. On the other hand, illegal means such as doping might shorten this process significantly. Modulating the brain by psychoactive drugs (neurodoping) might also influence motor skills and/ or learning processes. Recently, non-invasive brain stimulation (NIBS) such as transcranial direct current stimulation (tDCS) or transcranial magnetic stimulation (TMS) has also been shown to improve motor function and cognitive control. Hence, it seems reasonable to assume that NIBS might be an alternative strategy to facilitate sporting performance. However, I will discuss in this review that the application of NIBS in the context of sport should viewed with caution, especially because facilitatory NIBS effects have so far only been demonstrated in strictly controlled laboratory settings with partly variable outcomes and short-term after effects. Hence, it seems unlikely that NIBS might improve motor performance in a complex environment such as in sport competition. Furthermore, NIBS can also be associated with side effects and should therefore only be applied under strict medical guidance. Ethical aspects might also hinder its widespread application.